Spatial Effects of Industrial Effluent on Soil Quality around the Textile Industrial Area of Bhaluka Upazila, Mymensingh - Tabassum, N; Khatun, R; Baten, MA (Journal of Environmental Science and Natural Resources, 2016)
The study was carried out to investigate the spatial effects of industrial effluent on physico-chemical properties of soil around the textile industrial area of Bhaluka upazila, Mymensingh, from January to March, 2015. Total 15 soil samples were collected at 0m, 50m, 100m, 200m and 300m distances from the effluent discharging point. Soil texture, pH, electrical conductivity (EC), organic matter (OM), nitrogen (N), phosphorus (P), potassium (K), sulphur (S), sodium (Na) and heavy metal (lead, Pb and cadmium, Cd) content were investigated in this study. Soil pH, EC, OM and nutrient content of soil were higher at discharge point (at 0m) and lowest at 300m distance. The Pb content was maximum (36.9 ppm) at 0m and minimum (24.27 ppm) at 300m distance. The highest value (3.0 ppm) of Cd was observed at 0m and lowest value (2.8 ppm) was at 300m distance. All of the studied values were higher at the adjacent of industrial area and gradually decreased with distance. J. Environ. Sci. & Natural Resources, 8(2): 79-82 2015